Computational and experimental study of the combined effects of particle aspect ratio and effective diameter on flow behavior. (29th June 2022) - Yang, Jiecheng; Buettner, Kevin E.; DiNenna, Virginia L.; Curtis, Jennifer S.
Highlights: The Stress ratio from DEM matches SRST and Jenike measurement. The stress ratio depends on the particle equivalent diameter, length, and aspect ratio. Both particle alignment and solid fraction affect the flow behavior of elongated particles. Abstract: In this study, the flow behavior for various types of particles is investigated using Discrete Element Method (DEM), and the simulation predictions are compared with experimental results in Schulze Ring and Jenike shear tests. Specifically, the combined effect of particle size and particle aspect ratio on the ratio of shear to normal stress is explored in three cases: (1) particles with same equivalent diameter but different aspect ratios; (2) particles with same aspect ratio but different equivalent diameters; and (3) particles with same end-face diameter but different aspect ratios. Results show that the stress ratio depends largely on the degree of particle alignment in the first case, on the solids packing fraction in the second case, and on both particle alignment and packing fraction in the third case.